Re-thinking Gender Based Violence and its Implications on the Marriage Institution (Hekima Review, 2016)
The celebration of marriage manifests a union of love, joy and great intimacy. As both a sacrament and covenant, marriage is traceable back to its origin, God, who is Love. Despite this, recent studies on the marriage institution reveal that speaking of marriage as an exclusive union of love, joy, and great intimacy risks being termed a contradiction amidst the experiences of violence today. This paper focuses on gender based violence to argue that not only does gender based violence in marriages risk the health and wellbeingof the couple, children and the society, but also threatens the realization of the essential properties of marriage. Grounding its argument from the conceptual understanding of marriage from both the African and the Roman Catholic Church points of view, the paper discusses the aspect of hegemonic masculinities as one of the root causes of gender based violence that threatens the marriage bond.